Peningkatan Literasi Keuangan Digital Dan Keterampilan Daur Ulang Plastik Bagi Pengurus Bank Sampah Sumber Jaya Kranggan Bekasi - Rinny yudowati; Suhikmat; Akalily Mardhyya (Jurnal Pengabdian kepada Masyarakat UBJ, 2026)
This Community Service Program (Program Pengabdian kepada Masyarakat/PMP) for the 2025 funding year was conducted at the Sumber Jaya Krangan Waste Bank, Bekasi, with the aim of improving digital financial literacy and plastic waste processing skills among waste bank managers and members. The main problems faced by the partner included manual financial transaction recording, limited understanding of digital-based financial management, and insufficient skills in processing plastic waste into economically valuable products. The program employed a participatory training approach consisting of (1) digital financial recording training using a simple Excel Macro-based template, (2) training on processing plastic bags into handicraft products, and (3) mentoring on basic marketing of recycled products. Program evaluation was carried out through pre-tests, post-tests, and observation of participants’ competencies and product outputs. The results showed that approximately 80% of participants experienced improvements in their understanding and skills in digital financial recording and were able to produce recycled products suitable for introduction within the local community. These outcomes indicate that waste bank managers have begun to manage administrative activities and waste processing in a more structured manner. This improvement represents an initial step toward strengthening the role of waste banks as sustainable community-based economic units